Pelatihan dalam Menumbuhkan Ekonomi Kreatif Masyarakat Dusun Karang Melalui Pengelolaan Bank Sampah - Ridho, Maulana Miftakhu; Azzahra, Arthamevia Putri; Astriati, Dilla Putri; Andriansyah, Muhammad Helmi; Muhammad, Tsuraya Hasna’; Hasan, Farid (Penamas: Journal of Community Service, 2024)
Public awareness of waste processing is difficult to handle correctly. A simple alternative carried out by the people of Karang Hamlet, Rejosari Village, Bandongan District, Magelang Regency is the existence of a waste bank program. The need for more public understanding regarding waste bank management is the main target of implementing community service in Karang Hamlet. The aim is to improve the household economy and increase people's skills in processing waste through recycling inorganic waste. Apart from being beneficial for improving the community's economy, waste processing is also beneficial for the environment. The method used to provide understanding to the public regarding waste processing procedures is by conducting creative economy training in waste bank management. The result of this community service is an increase in the skills of the people of Karang Hamlet in processing inorganic waste with high selling value, as well as increasing public awareness of the importance of maintaining a clean and healthy environment. This activity also teaches the community about managing waste banks properly, which helps improve the community's economy.